Construction of Cu2O@Cu1.75S Core‐shell Octahedrons for Enhanced NO2 Gas Sensing at Low Temperature. Issue 10 (14th April 2022) - Zhang, Xiaohui; Li, Ping; Zhang, Ziwei; Guo, Jinghan; Fang, Zhongying; Ligani Fereja, Shemsu; Liu, Kaifan; Tong, Xinjie; Zheng, Yue; Li, Zongjun; Chen, Wei
Abstract: In this work, fabrication of Cu2 O@Cu1.75 S core‐shell octahedrons was achieved through a facile water bath stirring process. Compared with pure Cu2 O, the composite showed enhanced sensing performance for NO2 . The response value of Cu2 O@Cu1.75 S to 5 ppm NO2 at 40 °C is seven times that of Cu2 O to 5 ppm NO2 at 75 °C. Moreover, Cu2 O@Cu1.75 S has the ability to detect 100 ppb NO2 and has good NO2 sensing selectivity and long‐term stability. This study shows that Cu2 O@Cu1.75 S hybrid is a type of outstanding NO2 gas sensing material on account of its low working temperature and high sensing sensitivity. Abstract :